Genetic divergency on Common bean under tropical winter conditions - Ferrão, Maria Amélia Gava; Vieira, Clibas; Cruz, Cosme Damião; Cardoso, Antônio Américo (Pesquisa Agropecuaria Brasileira, 2002)
This work aimed to evaluate the genetic divergency among tolerants and non tolerants parents to cold and their hybrid combinations. The generalized distance of Mahalanobis, the method of cluster analysis proposed by Tocher and the canonical variability technic were the multivaried procedures used. Common bean cultivars of two different groups were used in the crosses, being Vermelho 2157, Ouro Negro, Antióquia 8 and Ricopardo 896 the cultivars tolerant to cold, and the commercial cultivars EMCAPA 404 – Serrano, Carioca and EMCAPA 405 – Goytacazes the non tolerant ones. The parents and the hybrid combinations in the F1, F2 and F3 generations were evaluated in Coimbra, Minas Gerais on four experiments, in 1995 and 1996. The genetic divergency among the genetic resources evaluated were influenced by temperature and advancement of the generations. The most dissimilar cultivars were Antióquia 8 and EMCAPA 404 – Serrano and Ouro Negro and Ricopardo 896 were the most similar cultivars. Grain yield and number of pods per plot were the less important characteristics influencing on genetic divergency. However, as they showed low genotypic correlation with the other characteristics and were of the greatest importance on yield, they can not be despised.